Harro - Koskinen, Harro; Tykkyläinen, Mia; Immonen, Kari; Ahlström-Taavitsainen, Camilla; Miller, Erik; Turun taidemuseo (Turun taidemuseon julkaisuja, ISSN 0789-9610, 2007)
Summary.
Keywords: Koskinen, Harro, : 1945-; näyttelyjulkaisut; taidenäyttelyt; kuvataide; underground; poptaide; henkilöhistoria; kuvataiteilijat; utställningskataloger; konstutställningar; bildkonst; popkonst; personhistoria; bildkonstnärer